Is endoscopic sinus surgery sufficient to modify the evolution of adult AERD? Aspirin desensitization as a maintenance factor: systematic review - Conti, Diego M.; Correa, Eduardo J.; Scadding, Glenis K. (Frontiers in Allergy, 2023)
Introduction Aspirin desensitization (AD) and aspirin therapy after desensitization (ATAD) are therapeutic interventions for patients with aspirin-exacerbated respiratory disease (AERD). Our aim is to investigate whether its addition to endoscopic sinus surgery (ESS) improves the overall prognosis of the disease. Methods A systematic review of the current literature including adult patients with a positive diagnosis of AERD undergoing endoscopic sinus surgery (ESS) in the context or in absence of upper airway comorbidity, prior to AD + ATAD. Conclusion This review concludes that the surgical approach is beneficial in AERD, but its effects are short—lived. Surgery should be considered initially with subsequent AD + ATAD in AERD patients, due to the sustained improvement achieved compared to those receiving ESS alone.